A2-D-A1-D-A2-type small molecule acceptors incorporated with electron-deficient core for non-fullerene organic solar cells. (February 2020) - Zhang, Min; Zeng, Min; Chen, Huajie; Li, Lanyan; Zhao, Bin; Tan, Songting
Highlights: Two new non-fullerene acceptor materials were designed and synthesized. A noncovalent conformational lock was formed between BT and IDT unit. A power conversion efficiency of 10.52% was obtained based on PBDB-T: BT-dIDT OSCs. Abstract: Two A2 -D-A1 -D-A2 -type small molecule acceptors (SMAs), DFB-dIDT and BT-dIDT with 2, 5-difluorobenzene (DFB) or benzothiadiazole (BT) as electron-withdrawing core (A1 ) and a derivative of indanone as A2 units, were prepared for applications in organic solar cells (OSCs). The results indicate that BT unit is more beneficial to forming multiple noncovalent conformational locks of N⋯S and N⋯H between BT and IDT unit than DFB in the core, so BT-dIDT showed better molecular coplanarity, higher-lying HOMO energy level, more red-shifted spectrum, superior molar absorption coefficient (1.60 × 10 5 M −1 cm −1 at 696 nm), more complementary absorption spectrum with PBDB-T and better photovoltaic performance than DFB-dIDT . As a result, the BT-dIDT-based OSCs blending with PBDB-T exhibited higher power conversion efficiency (PCE) value of 10.52% with higher J sc of 18.59 mA cm −2 than that of the DFB-dIDT -based devices (PCE of 6.71% with J sc of 15.58 mA cm −2 ). These results demonstrate that the A2 -D-A1 -D-A2 -type SMAs incorporated with a suitable electron-deficient core are promising candidates for high performance OSCs.